Propriedades extrínsecas em filmes finos de VO2 - Callegari, Gustavo Luiz (2010)
In earlier work done at the Laboratory of Magnetism and Magnetic Materials in Santa Maria, spectroscopy measurements of electrical impedance between 100 kHz and 1 GHz were a function of temperature in VO2 thin films along the metal insulator transition undergone by this material. These results suggested [127] that the Impedance Spectroscopy can be a useful tool to separate the contributions from those intrinsic material generated by morphological characteristics. For that such possibility could be actually realized, technological improvements were introduced in the system deposited by Magnetron Sputtering at Laboratory of Magnetism and Magnetic Materials as the addition of a Residual Gas Analyzer and improvements in the heating substrate holder. Spectroscopy measurements were performed in a wider range of frequencies and relaxation times extracted from them were compared with the structural characteristics of the samples obtained by X-ray diffraction and Atomic Force Spectroscopy.